Method for regulating and controlling particle size of platinum alloy in catalyst by using surfactant compound
By regulating the particle size of the platinum alloy in the catalyst using a composite of PVP and surfactant, the problem of easy agglomeration of the platinum-based alloy catalyst during high-temperature sintering is solved, and the preparation of a platinum-based alloy catalyst with small size, high activity and high stability is achieved.
Patent Information
- Application Number
- CN202411712181.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing platinum-based alloy catalysts are prone to agglomeration during high-temperature sintering, resulting in insufficient activity and stability of the catalyst, limiting their commercial application.
The catalyst precursor is regulated by a composite of polyvinylpyrrolidone (PVP) and surfactant. Through the synergistic action of electrostatic and coordination bonds, the agglomeration between particles is prevented and small-sized carbon-coated platinum-based alloy nanoparticles are formed.
It effectively prevents the agglomeration of platinum alloy particles, improves the activity and stability of the catalyst, extends its service life, simplifies the preparation process, and reduces costs.
Smart Images

Figure CN119601691A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for regulating the particle size of a platinum alloy, and belongs to the field of new energy materials. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have the advantages of low operating temperature, high power density, fast startup speed and environmental friendliness, making them an ideal power source for portable electronic devices and electric vehicles. Carbon-supported platinum (Pt)-based nanomaterials are the most common ORR catalysts in PEMFCs, however, their high price and poor durability limit their large-scale commercial application.
[0003] The ordered arrangement of atoms in the structure of intermetallic compounds gives Pt-based intermetallic compounds stronger strain and ligand effects. The long-range periodic crystal structure and clear stoichiometry of intermetallic compounds give them good chemical stability. Compared with Pt / C catalysts, they have excellent catalytic activity and stability. However, intermetallic compounds are more difficult to produce because the transition from disordered alloys to intermetallic compound structures usually requires high-temperature annealing above 500°C. High temperatures accelerate metal sintering, causing nanostructure deformation and agglomeration to form larger particles, limiting the commercial application of platinum-based intermetallic compounds. The carbon shell structure introduced by carbon coating technology can improve the anti-agglomeration ability of nanoparticles, inhibit the detachment, dissolution, and growth of metal particles during long-term use of catalysts, and improve the stability of catalysts. In order to control the thickness of the carbon layer or expose more active sites of the catalyst, the existing carbon coating technology will remove the carbon shell, which makes the preparation process of the catalyst complicated and the preparation cost increased. Therefore, it is of great value and significance to develop an alloy fuel cell catalyst with uniform metal particle distribution, uniform size, appropriate carbon layer thickness and simple preparation process. Summary of the invention
[0004] The present invention aims to solve the technical problem that the alloy is easy to agglomerate during the high-temperature sintering process of the existing platinum-based alloy catalyst, and provides a method for regulating the particle size of the platinum alloy in the catalyst by using a surfactant complex. The present invention uses a complex of polyvinyl pyrrolidone (PVP) and a surfactant to regulate the catalyst precursor. The surfactant is adsorbed on the surface of the catalyst precursor particles by electrostatic action, and the carbonyl groups in the molecules such as PVP can form coordination bonds with metal ions. The two act synergistically, which can effectively prevent the agglomeration between particles, so that the catalyst precursor forms smaller particles in the solution, thereby preventing the agglomeration of platinum alloy particles. Then, a carbon shell structure is obtained by high-temperature heat treatment to inhibit the migration and atomic movement of metal atoms, and a small-sized, highly active platinum-based alloy catalyst is obtained. The platinum-based alloy catalyst is represented by PtM / C, where M is Co, Ni, Cu or Fe.
[0005] The method of the present invention for regulating the particle size of platinum alloy in a catalyst by using a surfactant complex is carried out according to the following steps:
[0006] 1. Adding polyvinyl pyrrolidone (PVP) and the surfactant to the solvent at a mass ratio of 1:(0.3-3), and mixing them evenly to obtain a mixed solution; stirring the mixed solution at a temperature of 25-40° C. for 0.5-3 hours to obtain a complex solution;
[0007] 2. adding the carbon carrier to the composite solution prepared in step 1, and performing ultrasonic dispersion to obtain a carbon dispersion;
[0008] 3. adding chloroplatinic acid and a transition metal salt to the carbon dispersion prepared in step 2, and stirring with ultrasonic waves to obtain a mixture;
[0009] 4. heating the mixture obtained in step 3 under stirring conditions to evaporate the solvent, and then grinding to obtain a solid powder;
[0010] 5. Place the solid powder in a high-temperature furnace, raise the temperature to 400-900°C in a hydrogen-argon mixed atmosphere and maintain it for 1-12 hours for calcination, then cool it to room temperature to obtain a platinum-based alloy catalyst with regulated platinum alloy particle size, represented by PtM / C, where M is Co, Ni, Cu or Fe.
[0011] Furthermore, the surfactant described in step 1 is sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB) or sodium dodecyl sulfonate.
[0012] Furthermore, the total concentration of polyvinyl pyrrolidone and surfactant in the mixed solution described in step 1 is 0.01-0.2 mol / L.
[0013] Furthermore, the solvent in step 1 is water, ethanol or methanol.
[0014] Furthermore, the carbon carrier described in step 2 is one or a combination of mesoporous carbon, XC72, ECJ-300 and ECJ-600 carbon powder.
[0015] Furthermore, the concentration of the carbon carrier in the carbon dispersion in step 2 is 3-4 mg / mL.
[0016] Furthermore, the ultrasonic dispersion time in step 2 is 1 to 4 hours.
[0017] Furthermore, the transition metal salt in step three is cobalt nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate, iron nitrate nonahydrate, cobalt chloride or cobalt sulfate.
[0018] Furthermore, the molar ratio of chloroplatinic acid to transition metal salt in step three is (3-0.5):1.
[0019] Furthermore, the ultrasonic stirring time in step three is 30 to 180 minutes.
[0020] Furthermore, the heating temperature in step 4 is 60-80°C.
[0021] The platinum-based alloy catalyst prepared by the above method is carbon-coated nano-PtM alloy particles uniformly supported on a carbon carrier, represented by PtM / C, wherein M is Co, Ni, Cu or Fe; the mass fraction of platinum in the catalyst is 10-40wt.%.
[0022] The present invention adopts a composite of PVP and a surfactant to regulate the particle size of the platinum alloy, and uses an impregnation evaporation method to uniformly load the metal salt on a carbon carrier. The composite of PVP and a surfactant is calcined at a high temperature to form a carbon shell structure, which inhibits the migration and movement of metal atoms in the catalyst, thereby forming a catalyst of small-sized carbon-coated PtM alloy nanoparticles with a particle size of 2.5 to 4.5 nm.
[0023] The beneficial effects of the present invention compared to the prior art are as follows:
[0024] (1) The complex of PVP and surfactant can reduce the catalyst particle size and improve its dispersibility, so that more active sites are exposed on the surface, thereby increasing the contact opportunity between reactants and active sites and improving the activity of the catalyst.
[0025] (2) Under high-temperature calcination, alloy catalysts are prone to sintering and agglomeration, resulting in a reduction in active surface area and a decrease in catalytic performance. The complex of PVP and surfactant can form a protective layer on the surface of catalyst particles, preventing direct contact and sintering between particles, and improving the thermal stability of the catalyst.
[0026] (3) After adding the complex of PVP and surfactant, the binding force between the active component and the carrier is enhanced. After high-temperature calcination, a carbon shell structure is formed, making it more difficult for the active components of the PtM alloy particles in the catalyst to fall off during the reaction, thereby improving the stability of the catalyst and extending its service life.
[0027] (4) The present invention synthesizes a platinum-based catalyst with uniform particle size by regulating the complex of PVP and surfactant, and the mass activity of the catalyst is 0.14 to 0.33 mA / μg Pt The preparation method is simple to operate, low in cost, and can be mass-produced. It can be used in the field of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a TEM image of the platinum-based alloy catalyst prepared in Example 1;
[0029] Figure 2 is a particle size distribution diagram of the platinum-based alloy catalyst prepared in Example 1;
[0030] Figure 3 is a TEM image of the platinum-based alloy catalyst prepared in Comparative Example 1;
[0031] Figure 4 is a particle size distribution diagram of the platinum-based alloy catalyst prepared in Comparative Example 1;
[0032] Figure 5 is the XRD spectra of the platinum-based alloy catalysts prepared in Example 1 and Comparative Example 1;
[0033] Figure 6 is a polarization curve diagram of ORR of the platinum-based alloy catalysts prepared in Examples 1 to 3 and Comparative Example 1 and commercial Pt / C;
[0034] Figure 7 is a mass specific activity diagram of ORR of the platinum-based alloy catalysts prepared in Examples 1 to 3 and Comparative Example 1 and commercial Pt / C;
[0035] Figure 8 Graph showing the ORR polarization curves of the platinum-based alloy catalyst prepared in Example 1 and commercial Pt / C before and after aging. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0037] Example 1: The method of using a surfactant complex to control the particle size of a platinum alloy in a catalyst in this example is carried out according to the following steps:
[0038] 1. Add 0.4 g of polyvinylpyrrolidone (PVP) and 0.8 g of hexadecyltrimethylammonium bromide into 120 ml of deionized water, mix well, and obtain a mixed solution; then react the mixed solution in a constant temperature water bath at 30° C. for 2 h to obtain a complex solution;
[0039] 2. Add 200 mg of carbon powder ECJ300 to 60 ml of the complex solution prepared in step 1, and disperse by ultrasonic for 30 min to obtain a carbon dispersion;
[0040] 3. adding 5.74 ml of 9.24 mg / ml chloroplatinic acid aqueous solution and 80.6 mg of cobalt nitrate hexahydrate to the carbon dispersion prepared in step 2, and stirring for 1 hour under ultrasonic stirring to obtain a mixture;
[0041] 4. Stir the mixture obtained in step 3 in a water bath at 60° C. to evaporate the solvent, and grind for 5 min to obtain a solid powder;
[0042] 5. The solid powder is placed in a tubular furnace, and in a hydrogen-argon mixed atmosphere, the temperature is raised to 600°C and maintained for 2 hours for calcination, wherein the volume percentage of hydrogen in the hydrogen-argon mixed gas is 5%; the temperature is cooled to room temperature to obtain a platinum-based alloy catalyst with regulated platinum alloy particle size, denoted by PtCo / C.
[0043] Comparative Example 1: This comparative example is to directly use ECJ300 to load PtCo nanoparticles by impregnation method. The preparation method of the catalyst of this comparative example is carried out according to the following steps:
[0044] 1. Add 200 mg of carbon powder ECJ300 into 60 ml of water and disperse by ultrasonic for 30 min to obtain a carbon dispersion;
[0045] 2. adding 5.74 ml of 9.24 mg / ml chloroplatinic acid aqueous solution and 80.6 mg of cobalt nitrate hexahydrate to the carbon dispersion prepared in step 1, and stirring for 1 hour under ultrasonic stirring to obtain a mixture;
[0046] 3. Stir the mixture obtained in step 2 in a water bath at 60° C. to evaporate the solvent, and grind for 5 minutes to obtain a solid powder;
[0047] Fourth, the solid powder was placed in a tubular furnace, and heated to 600°C and maintained for 2 hours in a hydrogen-argon mixed atmosphere for calcination, wherein the volume percentage of hydrogen in the hydrogen-argon mixed atmosphere was 5%; the temperature was cooled to room temperature to obtain a platinum-based alloy catalyst for comparison.
[0048] The transmission electron microscope photo of the platinum-based alloy catalyst prepared in Example 1 is as follows: Figure 1 The particle size distribution diagram is shown in Figure 2 As shown, from Figure 1 It can be seen that the platinum-based alloy particles are evenly distributed without obvious agglomeration. Figure 2 It can be seen that the average particle size of the platinum-based alloy nanoparticles is 3.38 nm.
[0049] The transmission electron microscope photo of the platinum-based alloy catalyst prepared in Comparative Example 1 is as follows: Figure 3 The particle size distribution diagram is shown in Figure 4 As shown, from Figure 3 It can be seen that the distribution of platinum-based alloy particles is uneven, and there is obvious agglomeration. Figure 4It can be seen that the average particle size of the platinum-based alloy nanoparticles is 5.24 nm, which verifies that the addition of the composite of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide controls the particle size of the catalyst and improves the particle uniformity.
[0050] The XRD spectra of the platinum-based alloy catalyst PtCo / C prepared in Example 1 and the platinum-based alloy catalyst prepared in Comparative Example 1 are as follows: Figure 5 As shown, from Figure 5 It can be seen that the XRD test results are compared with the standard PDF card, which proves that both Example 1 and Comparative Example 1 synthesized PtCo alloys, and the addition of the composite of PVP and surfactant does not affect the crystal structure of the catalyst alloy.
[0051] Example 2: This example is to prepare a Pt3Co / C catalyst, and the specific method is carried out according to the following steps:
[0052] 1. Add 0.4 g of polyvinylpyrrolidone (PVP) and 0.8 g of hexadecyltrimethylammonium bromide into 120 ml of deionized water, mix well, and obtain a mixed solution; then react the mixed solution in a constant temperature water bath at 30° C. for 2 h to obtain a complex solution;
[0053] 2. Add 200 mg of carbon powder ECJ300 to 60 ml of the complex solution prepared in step 1, and disperse by ultrasonic for 30 min to obtain a carbon dispersion;
[0054] 3. adding 5.74 ml of 9.24 mg / ml chloroplatinic acid aqueous solution and 25.6 mg of cobalt nitrate hexahydrate to the carbon dispersion prepared in step 2, and stirring by ultrasonic for 1 hour to obtain a mixture;
[0055] 4. Stir the mixture obtained in step 3 in a water bath at 60° C. to evaporate the solvent, and grind for 5 min to obtain a solid powder;
[0056] 5. The solid powder is placed in a tubular furnace, and in a hydrogen-argon reducing atmosphere, the temperature is raised to 600°C and maintained for 2 hours for calcination, wherein the volume percentage of hydrogen in the hydrogen-argon mixture is 5%; the temperature is cooled to room temperature to obtain a platinum-based alloy catalyst with regulated platinum alloy particle size, denoted by Pt3Co / C.
[0057] Example 3: This example provides a method for preparing a PtCu / C catalyst, comprising the following steps:
[0058] 1. Add 0.4 g of polyvinylpyrrolidone (PVP) and 0.8 g of hexadecyltrimethylammonium bromide into 120 ml of deionized water, mix well, and obtain a mixed solution; then react the mixed solution in a constant temperature water bath at 30° C. for 2 h to obtain a complex solution;
[0059] 2. Add 200 mg of carbon powder ECJ300 to 60 ml of the complex solution prepared in step 1, and disperse by ultrasonic for 30 min to obtain a carbon dispersion;
[0060] 3. Add 5.89 ml of 9.24 mg / ml chloroplatinic acid aqueous solution and 67.5 mg of copper nitrate trihydrate to the carbon dispersion prepared in step 2, and stir ultrasonically for 1 hour to obtain a mixture;
[0061] 4. Stir the mixture obtained in step 3 in a water bath at 70° C. to evaporate the solvent, and grind for 5 min to obtain a solid powder;
[0062] 5. The solid powder is placed in a tubular furnace, and in a hydrogen-argon mixed atmosphere, the temperature is raised to 700°C and maintained for 2 hours for calcination, wherein the volume percentage of hydrogen in the hydrogen-argon mixed gas is 5%; the temperature is cooled to room temperature to obtain a platinum-based alloy catalyst with regulated platinum alloy particle size, represented by PtCu / C.
[0063] The platinum-based alloy catalyst PtCo / C prepared in Example 1, the platinum-based alloy catalyst Pt3Co / C prepared in Example 2, the platinum-based alloy catalyst PtCu / C prepared in Example 3, the platinum-based alloy catalyst prepared in Comparative Example 1 and a commercial 20% Pt / C catalyst (Comm. 20% Pt / C) purchased directly from a certain enterprise were subjected to ORR polarization test. The ORR polarization diagram was measured by step voltammetry (LSV) in an oxygen-saturated 0.1M HClO4 electrolyte with a potential range of 0.05-1.2V and a rotation speed of 1600rpm. The obtained ORR polarization curve is shown in the figure below: Figure 6 The mass activity diagram is shown in Figure 7 shown.
[0064] sample Element <![CDATA[Mass activity (MA) (mA / μg Pt) > Example 1 PtCo / C 0.28 Example 2 <![CDATA[Pt3Co / C]]> 0.145 Example 3 PtCu / C 0.33 Comparative Example 1 0.107 Commercial 20% Pt / C catalyst 0.108
[0065] from Figure 6 It can be seen that the half-wave of the catalysts (PtCo / C, Pt3Co / C, PtCu / C) with the addition of PVP and surfactant complexes is significantly higher than that of the catalyst without the addition of the complex in Comparative Example 1 and the commercial 20% Pt / C catalyst, proving that the addition of PVP and surfactant complexes improves the electrochemical performance of the catalyst.
[0066] From Table 1 and Figure 7 It can be seen that the mass activity (MA) of the platinum-based alloy catalyst PtCo / C prepared in Example 1 is 0.28 mA / μg Pt , which is about 2.5 times of the latest commercial 20% Pt / C; the mass activity of the platinum-based alloy catalyst Pt3Co / C prepared in Example 2 is 0.145mA / μg Pt, slightly higher than commercial 20% Pt / C; the mass activity of the platinum-based alloy catalyst PtCu / C prepared in Example 3 is 0.33A / mg Pt , which is about 3.0 times that of commercial 20% Pt / C.
[0067] The platinum-based alloy catalyst PtCo / C prepared in Example 1 and a commercial 20% Pt / C catalyst (Comm. 20% Pt / C) purchased directly from a certain enterprise were subjected to an ORR aging performance test. The aging test was conducted by conducting a potential cycle in an oxygen-saturated 0.1M HClO4 electrolyte to study the stability of the catalyst. The scan rate was 1 and the scan range was 0.6-1.0V. The ORR polarization diagrams before and after aging were as shown in FIG. Figure 8 As shown, from Figure 8 It can be seen that the stability of the platinum-based alloy catalyst PtCo / C prepared in Example 1 is much better than that of commercial 20% Pt / C. After 30,000 cycles of aging, the half-wave only drops by 4 mv, showing excellent stability.
[0068] The present invention introduces a complex of PVP and a surfactant, reduces the particle size of the catalyst and improves its dispersibility, so that more active sites are exposed on the surface, thereby increasing the contact opportunities between the reactants and the active sites and improving the activity of the catalyst; the binding force between the active component and the carrier is enhanced, and the metal salt is uniformly adsorbed on the surface of the carbon carrier by the impregnation evaporation method. The complex of PVP and the surfactant forms a protective layer on the surface of the catalyst particles to prevent direct contact and sintering between the particles. After high-temperature calcination treatment, the complex of PVP and the surfactant forms a carbon shell, making it more difficult for the active components of the metal particles in the catalyst to fall off during the reaction, thereby improving the stability of the catalyst and extending its service life. The present invention successfully prepares a small-sized, carbon-coated platinum-based alloy catalyst with simple operation and low cost.
Claims
1. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex, characterized in that: The method proceeds as follows:
1. Adding polyvinyl pyrrolidone and the surfactant to the solvent at a mass ratio of 1:(0.3-3), and mixing them evenly to obtain a mixed solution; stirring the mixed solution at a temperature of 25-40° C. for 0.5-3 h to obtain a complex solution; 2. adding the carbon carrier to the composite solution prepared in step 1, and dispersing by ultrasonic to obtain a carbon dispersion; 3. adding chloroplatinic acid and a transition metal salt to the carbon dispersion prepared in step 2, and stirring with ultrasonic waves to obtain a mixture; 4. heating the mixture obtained in step 3 under stirring conditions to evaporate the solvent, and then grinding to obtain a solid powder; 5. The solid powder is placed in a high-temperature furnace, heated to 400-900°C in a hydrogen-argon mixed atmosphere and maintained for 1-12 hours for calcination, and then cooled to room temperature to obtain a platinum-based alloy catalyst with regulated platinum alloy particle size.
2. The method for controlling the particle size of platinum alloy in a catalyst by using a surfactant complex according to claim 1, characterized in that: The surfactant described in step 1 is sodium dodecyl sulfate, hexadecyltrimethylammonium bromide or sodium dodecyl sulfonate.
3. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The total concentration of polyvinyl pyrrolidone and surfactant in the mixed solution described in step 1 is 0.01-0.2 mol / L.
4. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The solvent described in step 1 is water, ethanol or methanol.
5. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The carbon carrier described in step 2 is one or a combination of mesoporous carbon, XC72, ECJ300 and ECJ600 carbon powder.
6. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The concentration of the carbon carrier in the carbon dispersion described in step 2 is 3-4 mg / mL.
7. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The ultrasonic dispersion time in step 2 is 1 to 4 hours.
8. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The transition metal is Co, Ni, Cu or Fe.
9. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The transition metal salt is cobalt nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate, cobalt chloride, cobalt sulfate or ferric nitrate nonahydrate.
10. A method for regulating the particle size of platinum alloy in a catalyst using a surfactant complex according to claim 1 or 2, characterized in that: The molar ratio of chloroplatinic acid to transition metal salt is (3-0.5):1.
Citation Information
Cited By
Oxygen reduction electrocatalyst as well as preparation method and application thereof
CN119920911A
Method for preparing platinum-based alloy catalyst by using plasma enhanced chemical vapor deposition low-temperature technology
CN120453394A